The competitiveness of games in professional sports leagues - Wills, C. E. (Journal of Sports Analytics, 2017)
A sports game is about competition. The competitiveness of a game is important in terms of fan interest. Teams ahead or behind in a non-competitive game may also be more likely to substitute reserve players to reduce risk of injury to key players or gain experience for lesser-used players. Changes in how a team plays in a non-competitive game also impact secondary competitions such as betting or fantasy sports due to player behavior changes in a non-competitive game. This work examines the competitiveness of games in six professional sports leagues using a variety of metrics and finds that Major League Baseball (MLB) games are clearly the least competitive compared with games from each of the other leagues in our study. MLB games have the highest percentage of game segments that are played in less competitive situations. Major League Soccer and Barclay`s Premier League games tend to be the most competitive in general; largely because about half of game time for these leagues is spent with the game tied. However, if a team does take the lead in one of these leagues then they, along with MLB, have the highest chance that this team will not relinquish the lead.